REDESAIN TERMINAL SERUNI DENGAN PENEKANAN SISTEM WAYFINDING DI CILEGON, BANTEN - Yudistira Miranti Lestari; Tri Joko Daryanto; Maya Andria Nirawati (ARSITEKTURA, 2016)
Bus terminal in its role to help facilitating transportation activities especially in the distribution process of passengers in a city currently is not functioning optimally, as happened in Terminal Seruni Cilegon, Banten. Terminal which has supported regional scale transportation services (categorized as B type) with additional operating for AKAP, it’s still categorized as C-type terminal with an area of + 2 hectares, so that, both of main and supporting facilities have not been able to accommodate the functions of the current terminal activities. The function of this terminal which is still lacking, stimulate a behavior of public transportation, buses and passengers were reluctant to enter the terminal, instead they are moving to an area outside the Terminal, especially at area of Cilegon highway, which cause traffic jams in the area. The design issue is how to make a redesign concept of Terminal Seruni in Cilegon, Banten with the emphasis of wayfinding systems in facilitating user’s mobility to provide efficient orientation. The objective is to improve the quality of the buildings and restore the function and activity of area of East Cilegon highway into the area of Terminal Seruni. The method used is a method of designing architecture with the emphasis of wayfinding system. The results obtained are re-design with the emphasis of wayfinding system in Terminal Seruni which is applied in the space program based on zoning and spatial layout to determine the user's movement; lane separation for pedestrians and vehicles which can be supported with tools to help the orientation; circulation that provides comfort and ease of movement for the user, both circulation of vehicles and humans so that it will increase the efficiency of circulation in Terminal Seruni; as well as the design of the building that representative through the presence of a landmark combined with a sign or other additional sensors to strengthen the identity of Terminal Seruni. Keywords: Re-design, Bus Terminal, Wayfinding Systems, Efficiency Of Circulation